Using Advertising Value as The Stimulus Consumers to Change from Trial Action to Repurchase Action - Diem Phan, Quynh Thi; Nguyen, Phuong Van; Anh Le, Khoa Ngoc; Vu, Ngan Tuyet (International Journal of Supply Chain Management, 2018)
The advertising value has become an integrated part of every business. Although numerous research has explored the effectiveness of advertising, the perceived online advertising value has not been explored completely in terms of consumers’ awareness and stimulatory behaviors in the emerging market like Vietnam. By using Partial Least Squares-Structural Equation Model (PLS-SEM) approach, this study aims to investigate the roles of advertising value in stimulating consumers to repurchase action. Based on the data analysis of 209 correspondents, the findings showed that most of the key antecedents to advertising value, such as informative-ness, irritation, credibility, personalization, involvement and interactivity have a positive impact on the online advertising value. However, other factor, entertainment, was negatively associated with the online advertising value. Finally, in turn the advertising value has both direct and indirect effects on repurchase action via trial action and customers’ awareness. The results eventually lead to the improvement in creating an appealing online advertisement.